Model Komunikasi Westley dan Maclean dalam Pembelajaran Kosakata Bahasa Jerman - Misnawaty Usman; Nurming Saleh; Himala Praptami Adys (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study aims to make the process of learning German vocabulary more interesting and easy to master. an alternative in learning vocabulary, namely using the Westley & Maclean communication model. The method used in this research is descriptive qualitative. Then data collection techniques were carried out through interviews, observation, and documentation. Based on the data obtained, an analysis and interpretation of the meaning of the data is carried out. The theory used is the Westley & Maclean communication model. The results of this study indicate that communication has an important role in learning German vocabulary. The proof can be seen in the communication model applied at SMA Negeri 14 Gowa. The applied learning communication has been designed systematically.